Processing tomato (Lycopersicon esculentum Miller) yield and quality in arid regions through micro-nano aerated drip irrigation coupled with humic acid application - Jiaying Ma; Rui Chen; Yue Wen; Jinzhu Zhang; Feihu Yin; Tehseen Javed; Jiliang Zheng; Zhenhua Wang (Agricultural Water Management)
The long-term, extensive use of mulched drip irrigation has effectively mitigated water scarcity. However, it has led to reduced soil aeration, with a negative impact on crop growth and yield. Our study aims to tackle this issue by investigating the arid region of Northwest China, focusing on how humic acid (HA)-based water-fertilizer-gas coupled drip irrigation influences soil aeration, as well as the yield and quality of processing tomatoes. The experiment involved two irrigation amounts (W1:450 mm, W2:380 mm), three HA application rates (H1: 0 %, H2: 0.25 %, H3: 0.5 %), and two aeration methods (A1: non-aerated, A2: micro-nano aerated). The finding of the study revealed that compared to the conventional treatment (W1H1A1), the synergistic application of 0.5 % HA combined with micro-nano aeration significantly improved both the yield and quality (vitamin C, soluble sugars, lycopene, and soluble solids, increased by 102.97 %, 38.95 %, 104.69 %, and 21.16 %, respectively) of processing tomatoes under low irrigation stress (380 mm) in the first year. Although the effect diminished under two years of low water irrigation, the treatment maintained a high yield (147.96 t ha–1). SEM analysis revealed that coupled water-fertilizer-gas drip irrigation directly enhanced soil oxygen content while negatively affecting soil water-filled porosity and evapotranspiration, thus indirectly influencing the growth, yield, and quality of processing tomatoes. Multiple regression and spatial analysis of yield, water use efficiency, and lycopene content indicated that, under micro-nano aeration, irrigation volumes between 445.700–446.833 mm, combined with 0.492–0.498 % HA, represent optimal irrigation strategies. These conditions ensured that yield (278.03–281.21 t ha–1), WUE (0.57–0.58 t ha–1 mm–1), lycopene content (56.28–56.76 mg kg–1), and Vc content (56.06–56.19 mg 100 g–1) remained above 95 % of their maximum values.